2018
DOI: 10.1016/j.erss.2018.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Getting on the ground: Exploring the determinants of utility-scale solar PV in Rwanda

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…In 2018, renewable energy generation capacity in Africa stood at about 50 GW, primarily derived from hydropower (35 GW), wind (5.5 GW), solar PV (4.5 GW) and geothermal (0.7 GW) [3]. However, as stated by Rodriguez-Manotas et al [6], several East African countries which are heavily reliant on hydro for electricity generation, are shifting towards other renewable energy sources due to the depletion of water resources and successive droughts. The IRENA [7] reported global weighted average cost reductions of 69% in the electricity generation of utility-scale solar PV plants and 18% for onshore wind electricity generation between 2010 and 2016.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, renewable energy generation capacity in Africa stood at about 50 GW, primarily derived from hydropower (35 GW), wind (5.5 GW), solar PV (4.5 GW) and geothermal (0.7 GW) [3]. However, as stated by Rodriguez-Manotas et al [6], several East African countries which are heavily reliant on hydro for electricity generation, are shifting towards other renewable energy sources due to the depletion of water resources and successive droughts. The IRENA [7] reported global weighted average cost reductions of 69% in the electricity generation of utility-scale solar PV plants and 18% for onshore wind electricity generation between 2010 and 2016.…”
Section: Introductionmentioning
confidence: 99%
“…On the supply side, especially for the large-scale infrastructure cluster, it is private investors who are driving the transition in low-income countries (Nygaard et al, 2017). As such, donors now play a predominantly supporting role in many lowincome countries, to kick-start and de-risk projects that otherwise operate on commercial grounds (Rodríguez-Manotas et al, 2018). This movement -from projects to markets -creates new challenges and opportunities for governments, and their development partners, to optimise the enabling framework for low-carbon energy technologies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the statistically analysed data from questionnaires showed that 43.6% of all households incurred FRW 500 and 21.0% incurred FRW 1000, monthly electricity bills, respectively (Rwanda Francs (FRW)). [3,52]. Additionally, the percentage of households having home appliances like television sets, radios, electric irons, and refrigerators were 39.6%, 91.1%, 14.9%, and 4.0% respectively.…”
Section: Off-grid Village Energy For Household Basic Needsmentioning
confidence: 99%